Three-dimensional characterization of the vascular bed in bone metastasis of the rat by microcomputed tomography (MicroCT). - Hervé Nyangoga; Philippe Mercier; Hélène Libouban; Michel Félix Baslé; Daniel Chappard (PLoS ONE, 2011)
BACKGROUND: Angiogenesis contributes to proliferation and metastatic dissemination of cancer cells. Anatomy of blood vessels in tumors has been characterized with 2D techniques (histology or angiography). They are not fully representative of the trajectories of vessels throughout the tissues and are not adapted to analyze changes occurring inside the bone marrow cavities. METHODOLOGY/PRINCIPAL FINDINGS: We have characterized the vasculature of bone metastases in 3D at different times of evolution of the disease. Metastases were induced in the femur of Wistar rats by a local injection of Walker 256/B cells. Microfil®, (a silicone-based polymer) was injected at euthanasia in the aorta 12, 19 and 26 days after injection of tumor cells. Undecalcified bones (containing the radio opaque vascular casts) were analyzed by microCT, and a first 3D model was reconstructed. Bones were then decalcified and reanalyzed by microCT; a second model (comprising only the vessels) was obtained and overimposed on the former, thus providing a clear visualization of vessel trajectories in the invaded metaphysic allowing quantitative evaluation of the vascular volume and vessel diameter. Histological analysis of the marrow was possible on the decalcified specimens. Walker 256/B cells induced a marked osteolysis with cortical perforations. The metaphysis of invaded bones became progressively hypervascular. New vessels replaced the major central medullar artery coming from the diaphyseal shaft. They sprouted from the periosteum and extended into the metastatic area. The newly formed vessels were irregular in diameter, tortuous with a disorganized architecture. A quantitative analysis of vascular volume indicated that neoangiogenesis increased with the development of the tumor with the appearance of vessels with a larger diameter. CONCLUSION: This new method evidenced the tumor angiogenesis in 3D at different development times of the metastasis growth. Bone and the vascular bed can be identified by a double reconstruction and allowed a quantitative evaluation of angiogenesis upon time.